2021
DOI: 10.1101/2021.12.14.472696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic remodeling during monolayer cell expansion reduces therapeutic potential

Abstract: Understanding how cells remember previous mechanical environments to influence their fate, or mechanical memory, informs the design of biomaterials and therapies in medicine. Current regeneration therapies require two-dimensional (2D) cell expansion processes to achieve large cell populations critical for the repair of damaged (e.g. connective and musculoskeletal) tissues. However, the influence of mechanical memory on cell fate following expansion is unknown, and mechanisms defining how physical environments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…Inhibiting the demethylase of H3K9me3, surprisingly, did not alter the peripheral enrichment of H3K9me3. We have previously found that ML324 applied at higher concentrations (10µM) to chondrocytes during the 2D expansion process causes an increase in dense regions of H3K9me3 toward the nuclear envelop and an increase in chondrogenic gene expression 9 . Therefore, we anticipated that treating the chondrocytes with ML324 prior to encapsulation would increase the chondrogenic phenotype in 3D culture.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Inhibiting the demethylase of H3K9me3, surprisingly, did not alter the peripheral enrichment of H3K9me3. We have previously found that ML324 applied at higher concentrations (10µM) to chondrocytes during the 2D expansion process causes an increase in dense regions of H3K9me3 toward the nuclear envelop and an increase in chondrogenic gene expression 9 . Therefore, we anticipated that treating the chondrocytes with ML324 prior to encapsulation would increase the chondrogenic phenotype in 3D culture.…”
Section: Discussionmentioning
confidence: 97%
“…Chondrocytes were encapsulated at a concentration of 10×10 6 cells/mL after isolation (PD0), 8 population doublings (PD8) and 16 population doublings (PD16) in 3D hyaluronan-poly(ethylene) glycol diacrylate (HA-PEGDA) hydrogels (20 mg/1mL of HA and 8.6 mg/mL PEGDA) and cultured for 1, 5, and 10 days as previously described 9 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations